Costs of photosynthesis and cellular remodeling in trophic transitions of the unicellular red alga Galdieria partita - Shota Yamashita; Shunsuke Hirooka; Takayuki Fujiwara; Baifeng Zhou; Fumi Yagisawa; Kei Tamashiro; Hiroki Murakami; Koichiro Awai; Shin-ya Miyagishima (Communications Biology)
Abstract As in plastid differentiation in land plants, some unicellular algae reversibly remodel photosynthetic plastids into a colorless heterotrophic state (bleaching) in the presence of organic carbon sources. To understand these mechanisms and their significance, we performed comparative omics analyses on the photoautotrophic and heterotrophic states and their transitions in the genetically tractable red alga Galdieria partita. Photoautotrophic cells require 1.5, 1.3 and 1.7 times more nitrogen, protein, and fatty acids than heterotrophic cells. In the photoautotrophic cells, plastid- and nucleus-encoded proteins for photosynthesis are highly synthesized, while in the heterotrophic state, cytoplasmic and mitochondrial proteins are more abundant, enabling 1.6 times faster growth. Changes in non-plastid metabolic enzymes are limited, with some upregulated in the photoautotrophic state to support fatty acid and glycolipid synthesis in the plastid for thylakoid membranes. In contrast, solute transporters show broader changes. Bleaching occurs upon adding certain sugars or sugar alcohols, regardless of light, not by active digestion of photosynthetic machinery, but by dilution due to suppressed synthesis at the transcriptional level and faster cell growth. Thus, when assimilable organic carbon is available, the cells repress the synthesis of proteins, lipids, and pigments for photosynthesis, reallocating resources to promote faster growth.